Step
*
1
1
of Lemma
es-prior-fixedpoints-causle
1. [Info] : Type
2. es : EO+(Info)@i'
3. X : EClass(Top)@i'
4. f : E(X) ─→ E(X)@i
5. ∀x:E(X). f x c≤ x@i
6. e : E(X)@i
7. ∀e1:E(X). ((e1 < e) 
⇒ (∀e':E(X). ((e' ∈ prior-f-fixedpoints(e1)) 
⇒ e' c≤ e1)))
8. (f e) = e ∈ E
9. ↑e ∈b prior(X)
10. e' : E(X)@i
11. (e' ∈ prior-f-fixedpoints(prior(X)(e)))@i
⊢ e' c≤ e
BY
{ ((Assert (prior(X)(e) <loc e) BY
          (BLemma `es-prior-interface-locl` THEN Auto))
   THEN (Assert e' c≤ prior(X)(e) BY
               (BackThruSomeHyp THEN Auto))
   THEN Auto) }
Latex:
Latex:
1.  [Info]  :  Type
2.  es  :  EO+(Info)@i'
3.  X  :  EClass(Top)@i'
4.  f  :  E(X)  {}\mrightarrow{}  E(X)@i
5.  \mforall{}x:E(X).  f  x  c\mleq{}  x@i
6.  e  :  E(X)@i
7.  \mforall{}e1:E(X).  ((e1  <  e)  {}\mRightarrow{}  (\mforall{}e':E(X).  ((e'  \mmember{}  prior-f-fixedpoints(e1))  {}\mRightarrow{}  e'  c\mleq{}  e1)))
8.  (f  e)  =  e
9.  \muparrow{}e  \mmember{}\msubb{}  prior(X)
10.  e'  :  E(X)@i
11.  (e'  \mmember{}  prior-f-fixedpoints(prior(X)(e)))@i
\mvdash{}  e'  c\mleq{}  e
By
Latex:
((Assert  (prior(X)(e)  <loc  e)  BY
                (BLemma  `es-prior-interface-locl`  THEN  Auto))
  THEN  (Assert  e'  c\mleq{}  prior(X)(e)  BY
                          (BackThruSomeHyp  THEN  Auto))
  THEN  Auto)
Home
Index